Maternal serum and cord blood anti-A and Anti-B antibody levels as a predictor of significant hyperbilirubinemia in newborns - Pramod Uttamlal Toshniwal; Lalitha Krishnan; Simon Kingsley; Satish Kurvila; M Manikandan (Asian Journal of Transfusion Science)
BACKGROUND: Hemolytic disease of the newborn (HDN) was more common due to Rh incompatibility. Its prevalence has decreased due to introduction of Immunoglobulin G (IgG) prophylaxis against RhD antigen. HDN due to ABO incompatibility has become more common. AIM: The aim of this study was to study the predictive value of umbilical cord serum and maternal serum anti-A and anti-B antibody titer for the occurrence of significant hyperbilirubinemia in newborns. SETTINGS AND DESIGN: This was a prospective cohort study which included 139 “O” blood group mothers and their offspring with A or B blood groups. MATERIALS AND METHODS: We analyzed the IgG anti-A, and anti-B antibody titers from cord blood and maternal serum and correlated them with features of significant hyperbilirubinemia. Positive predictive value (PPV), negative predictive value (NPV), sensitivity and specificity were calculated. RESULTS: Twenty-eight newborns out of 139 (20 %) developed significant hyperbilirubinemia and required phototherapy. One newborn required immunoglobulin infusion. Out of these 28 newborns’ maternal serum, 22 (79%) newborns’ maternal serum had IgG antibody titer of ≥128. Cord blood serum IgG antibody titer was 1:2 in all newborns, which was not significant. The direct Coombs test was positive in six (4%) newborns with maternal IgG antibody titer ≥128. CONCLUSION: Maternal IgG antibody titer was ≥1:128 and can predict significant hyperbilirubinemia in newborns with a sensitivity of 53.5%, specificity of 98.2%, PPV of 88%, NPV of 89%, and P value (P > 0.001).